Anesthetic Choice for Percutaneous Transcatheter Closure of the Left Atrial Appendage: A National Anesthesia Clinical Outcomes Registry Analysis - William Hickman; Rachel S. Dada; Dylan Thibault; Christina Gibson; Scott Heller; Vikrant Jagadeesan; Heather K. Hayanga (Annals of Cardiac Anaesthesia, 2024)
Context: Left atrial appendage closure (LAAC) was developed as a novel stroke prevention alternative for patients with atrial fibrillation, particularly for those not suitable for long-term oral anticoagulant therapy. Traditionally, general anesthesia (GA) has been more commonly used primarily due to the necessity of transesophageal echocardiography. Aims: Compare trends of monitored anesthesia care (MAC) versus GA for percutaneous transcatheter LAAC with endocardial implant and assess for independent variables associated with primary anesthetic choice. Settings and Design: Multi-institutional data collected from across the United States using the National Anesthesia Clinical Outcomes Registry. Material and Methods: Retrospective data analysis from 2017–2021. Statistical Analysis Used: Independent-sample t tests or Mann–Whitney U tests were used for continuous variables and Chi-square tests or Fisher’s exact test for categorical variables. Multivariate logistic regression was used to assess patient and hospital characteristics. Results: A total of 19,395 patients underwent the procedure, and 352 patients (1.8%) received MAC. MAC usage trended upward from 2017–2021 (P < 0.0001). MAC patients were more likely to have an American Society of Anesthesiologists (ASA) physical status of≥ 4 (33.6% vs 22.89%) and to have been treated at centers in the South (67.7% vs 44.2%), in rural locations (71% vs 39.5%), and with lower median annual percutaneous transcatheter LAAC volume (102 vs 153 procedures) (all P < 0.0001). In multivariate analysis, patients treated in the West had 85% lower odds of receiving MAC compared to those in the Northeast (AOR: 0.15; 95% CI 0.03–0.80, P = 0.0261). Conclusions: While GA is the most common anesthetic technique for percutaneous transcatheter closure of the left atrial appendage, a small, statistically significant increase in MAC occurred from 2017–2021. Anesthetic management for LAAC varies with geographic location.